Single-molecule assays reveal that RNA localization signals regulate dynein-dynactin copy number on individual transcript cargoes - Amrute-Nayak, Mamta (2012)
Subcellular localization of mRNAs by cytoskeletal motors plays critical roles in the spatial control of protein function(1). However, optical limitations of studying mRNA transport in vivo mean that there is little mechanistic insight into how transcripts are packaged and linked to motors, and how the movement of mRNA:motor complexes on the cytoskeleton is orchestrated. Here, we have reconstituted transport of mRNPs containing specific RNAs in vitro. We show directly that mRNAs that are either apically localized or non-localized in Drosophila embryos associate with the dynein motor and move bidirectionally on individual microtubules, with localizing mRNPs exhibiting a strong minus-end-directed bias. Single-molecule fluorescence measurements reveal that RNA localization signals increase the average number of dynein and dynactin components recruited to individual mRNPs. We find that, surprisingly, individual RNA molecules are present in motile mRNPs in vitro and present evidence that this is also the case in vivo. Thus, RNA oligomerization is not obligatory for transport. Our findings lead to a model in which RNA localization signals produce highly polarized distributions of transcript populations through modest changes in motor copy number on single mRNA molecules.